2020
DOI: 10.3390/insects11060341
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Flies as Pollinators of Horticultural Crops: An Australian Case Study with Worldwide Relevance

Abstract: Australian horticulture relies heavily on the introduced managed honey bee, Apis mellifera Linnaeus 1758 (Hymenoptera: Apidae), to pollinate crops. Given the risks associated with reliance upon a single species, it would be prudent to identify other taxa that could be managed to provide crop pollination services. We reviewed the literature relating to the distribution, efficiency and management potential of a number of flies (Diptera) known to visit pollinator-dependent crops in Australia and worldwide. Applyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
62
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 175 publications
0
62
0
1
Order By: Relevance
“…In addition to collecting nectar and other floral resources, bees (Hymenoptera: Apoidea: Anthophila) and some flies (Diptera) visit a wide diversity of flowering plants to gather pollen (Thorp, 2000; Woodcock et al ., 2014; Cook et al ., 2020). Pollen consumption is known in fly species in the families Bombyliidae, Empididae, Muscidae, Tabanidae, Ceratopogonidae, and particularly Syrphidae (Inouye et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to collecting nectar and other floral resources, bees (Hymenoptera: Apoidea: Anthophila) and some flies (Diptera) visit a wide diversity of flowering plants to gather pollen (Thorp, 2000; Woodcock et al ., 2014; Cook et al ., 2020). Pollen consumption is known in fly species in the families Bombyliidae, Empididae, Muscidae, Tabanidae, Ceratopogonidae, and particularly Syrphidae (Inouye et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported species-selective pollinator visitation to hybrid carrot seed crops including pollinators such as A. mellifera [2,3,[6][7][8], flies [9,10], Megachile bees [11], and other native bees [12], but there appear to be no reports on carrot pollinator assemblage level visitation to different CMS cultivars, despite strong indications of differences in pollinator attraction among cultivars [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Here we suggest including flies, when appropriate, in pollinator disease transmission dynamics, as the roles of flower-visiting flies has often been speculated but not tested. Cook et al 45 found that flies from 86 families have been reported visiting the flowers of more than 1100 different species of plants globally, however, flies are not the only insects sharing floral resources with bees.…”
Section: Discussionmentioning
confidence: 99%